Kemampuan Membaca Alquran dan Menghormati Orang Tua dengan Prestasi Belajar PAI Siswa SMP Surakarta - Wakhid Ichsanto; Retno Wahyuningsih (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2021)
The purposes of this research are knowing the correlation of the ability to read the Qur’an, the attitude of respect for parents on learning achievement. This research recruited 6 classes of students of Special Program Batik Junior High School Surakarta. Results show that (1) The correlation coefficient for the variable of the ability to read the Qur'an is 0.385 with a probability of 0.000, meaning that there is an influence of the ability to read the Qur'an on learning achievement. The magnitude of the influence of the ability to read Al-Qur'an on the learning achievement of Islamic Education is 14.8%. (2) The correlation coefficient for the variable the attitude of respect for parents is 0.634 with a probability of 0.000, meaning that there is an effect of respecting parents on learning achievement. (3) The magnitude of the effect of the attitude of respect for parents on the learning achievement of Islamic Education is 40.2%. The correlation coefficient for the ability to read the Qur'an and respect parents together is 0.440 with a probability of 0.000, meaning that there is an effect of the ability to read the Qur'an and respect parents together on the learning achievement of Islamic Education at the Surakarta Special Program Batik Junior High School in 2020.